NFLIK TANAH ADAT SAKAI DI KAMPUNG MANDIANGIN KECAMATAN MINAS KABUPATEN SIAK - Santika, Vira; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
his research was conducted in Mandiangin Village, Siak Regency with the aim of knowing the Sakai Customary Land Conflict in Mandiangin Village. This study uses descriptive qualitative research methods. In collecting data using observation research methods, in-depth interviews and also documentation. The handling of this Sakai customary land conflict is the establishment of the Sakai Mandiangin Traditional Village. To determine these customary rights, a measurement of the boundaries of the Mandiangin Village area was carried out which was attended by representatives from the villages directly adjacent to Mandiangin Village. With this map of the boundaries of the Mandiangin Village, it is known the location and extent of the customary rights of the Mandiangin Village community. The role of the Sakai Traditional Institution in Mandiangin Village will be further strengthened, because the regulations that will be applied in the Traditional Village are the local customary regulations, whereas for the Sakai Mandiangin Traditional Village it is the Sakai Customary Regulation. However, all customary regulations that are stipulated will refer to their conformity with government regulations and do not violate applicable norms. Keywords: Conflict, Traditional Village, Ulayat RightsMINAS